Holocene changes in forest composition in northern Patagonia responded to climate with little impact of disturbance - Valentina Andrea Álvarez-Barra; Thomas Giesecke; Sonia L Fontana (PANGAEA, 2021)
Here we present pollen and charcoal counts from a small lake located within the Lanín National Park, Argentina (40°12 extquotesingleS; 71°30 extquotesingleW; 1095 m a.s.l). The lacustrine sediment core was retrieved in January 2017. Pollen samples of 0.5 cm^3 were taken every 2 cm, avoiding tephra sections. Before and after major tephra layers the sampling was carried out at an interval of 1 cm. Processing of samples for pollen analysis was conducted following Bennett and Willis (2001; doi:10.1007/0-306-47668-1), including hydrofluoric acid and acetolysis. Samples with coarse particles were sieved at 120 μm. To reconstruct the past fire regime, macroscopic charcoal particles were counted in 1 cm^3 samples contiguously along the core at 1 cm intervals avoiding tephra layers wider than 1 cm. The samples were processed according to the methodology by Stevenson and Haberle (2005; hdl:1885/144170). Particles > 125 μm were counted under a binocular dissecting microscope (Whitlock and Anderson, 2003; doi:10.1007/0-387-21710-X_1).